Flow-Induced Wall Mechanics of Patient-Specific Aneurysmal Cerebral Arteries: Nonlinear Isotropic Versus Anisotropic Wall Stress - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2014)
Fluid-structure interaction simulations of three patient-specific models of cerebral aneurysms were carried out with the objective of quantifying the effects of non-Newtonian blood flow and the vessel mechanical behavior on the time-dependent fluid shear and normal stresses, and structural stress and stretch. The average wall shear stress at peak systole was found to be approximately one order of magnitude smaller than the shear stresses in the proximal communicating arteries, regardless of the shape or size of the aneurysms. Spatial distributions of oscillatory shear index were consistent with the reciprocal of wall shear stress distributions at peak systole for all aneurysm geometries, demonstrating that oscillatory shear index correlates inversely with wall shear at this time point in the cardiac cycle. An aneurysm wall modeled with an isotropic material resulted in an underestimation of both the maximum principal stress and stretch, compared to the anisotropic material model. For the three aneurysm geometries, anisotropic peak wall stresses were approximately 50% higher than for an isotropic material. Regardless of the constitutive material, the maximum stresses were consistently located at the aneurysm neck; stresses in the dome were 30% of those in the neck.